การคัดเลือกพันธุ์มันฝรั่งที่ต้านทานต่อโรคใบไหม้ - ฐิตาภรณ์ เรืองกูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Late blight disease of potato is caused by the fungus, Phytophthora infestans. Eighty-seven of ‘Atlantic’ potato leaf symptoms were observed and collected from the field at Mae Wang, Phrao and Mae Ai district in Chiang Mai Province and Mae Sai district in Chiang Rai Province in 2017 - 2018. Seven of eighty-seven leaves were collected in the rainy season and the rest in the winter season. Late blight symptoms were appeared water-soaked spot on leaf margin and developed to enlarge lesions. Lateral stem and main stem showed brown to black lesion, collapse and death. Isolation of fungal pathogen with inverted petri dish culture method on WA medium and transferred fungal mycelium onto corn A agar without adding antibiotics was found the most successful method for fungal isolation and could induce sporangium on corn A agar. Fifty isolates of fungi were isolated and only four isolates i.e. KW3, Phrao3, MA6 and MS8 were produced abundant sporangia on corn A agar. The four isolates were selected and identified by morphological characteristic, pathogenicity test under plant tissue culture condition and nucleotide sequence analysis of internal transcribed spacer (ITS) with primer ITS1/ITS4. The results of identification showed these 4 isolates were causing late blight disease in potato. Virulence of 4 fungal isolates were compared under plant tissue culture condition, the result showed that all isolates could infected in ‘Atlantic’ potato plantlet. However, the most virulence isolate (MA6) showed severe symptoms on leaves and stem. The fungal mycelia and sporangia were grew on infected area. Finally, these Atlantic potatoes were collapsed and dead after 9 days of inoculation.